The effectiveness of the transactional analysis on mental well-being and empathy in nurses: Effectiveness of the transactional analysis - Khalili-Tajareh, Rounak; Ahmadian, Hamzeh (Chronic Diseases Journal, 2025)
BACKGROUND: A healthy interpersonal relationship is a key contributor to nurses' success in their occupation. Hence, nurses who are equipped with essential interpersonal skills know how to treat patients with dignity and respect and do their jobs more effectively. Despite the rapidly growing body of research on various aspects of transactional analysis (TA), only a few studies have addressed the role of TA in the nursing area. This paper reports on a study that investigates the effectiveness of TA on mental well-being and empathy among nurses in Sanandaj, a city in the west of Iran. METHODS: This study adopted a quasi-experimental design and a pretest-posttest design. Using the available sampling method, 26 nurses were randomly assigned to an experimental a control group. The experimental group received two months of training in TA through eight 90-minute sessions. A questionnaire was used to collect data before and after the TA training program . RESULTS: There were statistically significant differences between the experimental and control groups in emotional (P ≤ 0.05), psychological (P ≤ 0.05), and social (P ≤ 0.01) well-being, reactive and verbal empathy (P ≤ 0.05), and emotional effectiveness (P ≤ 0.05). CONCLUSION: The findings of the study reveal that TA training can enhance the mental health of nurses effectively.